2022
DOI: 10.1109/access.2022.3160596
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Evaluation of Human Performance in Detecting Digital Face Image Manipulations

Abstract: In recent years, increasing deployment of face recognition technology in security-critical settings, such as border control or law enforcement, has led to considerable interest in the vulnerability of face recognition systems to attacks utilising legitimate documents, which are issued on the basis of digitally manipulated face images. As automated manipulation and attack detection remains a challenging task, conventional processes with human inspectors performing identity verification remain indispensable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Some of the more recent studies have provided important inputs in areas such as the potential trauma of collecting the victims’ DNA for their families [ 54 ], ethical inquiries [ 5 , 55 ], and psychological assessments [ 56 , 57 ]. An increasing body of social science research is currently available and more researchers are starting to focus on this area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the more recent studies have provided important inputs in areas such as the potential trauma of collecting the victims’ DNA for their families [ 54 ], ethical inquiries [ 5 , 55 ], and psychological assessments [ 56 , 57 ]. An increasing body of social science research is currently available and more researchers are starting to focus on this area of research.…”
Section: Discussionmentioning
confidence: 99%
“…This section briefly describes the experimental setup. Conducted experiments build upon the work of [18] to which the interested reader is referred to for more details. In order to fuse decisions of human examiners, they first participated in an experiment for detecting digital face image manipulations.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to automated detection systems, human performance for detecting digitally altered face images has been analysed in some previous works, e.g. in [9][10][11][12][13][14][15][16][17][18]. While research in the area of human face manipulation detection is relatively sparse, initial studies have indicated that humans display inadequate proficiency in detecting certain types of manipulated face images.…”
Section: Manipulated (Reject)mentioning
confidence: 99%
“…Nowadays, with the rapid development of various recognition technologies, more new technologies based on feature recognition are emerging. R. et al introduced a network-based remote visual recognition experiment, which aims to test human proficiency in detecting different kinds of digital image signals based on the principles adopted in psychophysics [13]. By manipulating facial images, especially face exchange, deformation, and modification, the pattern of human recognition image information can be further analyzed, which is helpful to improve the face recognition algorithm.…”
Section: Digital Image Processing In Human Feature Recognitionmentioning
confidence: 99%